Hidden Insurance in a Moral Hazard Economy - Giuseppe Bertola; Winfried Koeniger (Institute for the Study of Labor (IZA), 2013)
We consider an economy where individuals privately choose effort and trade competitively priced securities that pay off with effort-determined probability. We show that if insurance against a negative shock is sufficiently incomplete, then standard functional form restrictions ensure that individual objective functions are optimized by an effort and insurance combination that is unique and satisfies first- and second-order conditions. Modeling insurance incompleteness in terms of costly production of private insurance services, we characterize the constrained inefficiency arising in general equilibrium from competitive pricing of nonexclusive financial contracts.
Keywords: E21; D81; D82; 330; hidden action; principal agent; first-order approach; constrained efficiency